2011
DOI: 10.1186/1742-6405-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical monitoring and correlates of nephropathy in SIV-infected macaques during high-dose antiretroviral therapy

Abstract: BackgroundIn many preclinical AIDS research studies, antiretroviral therapy (ART) is administered to experimentally simian immunodeficiency (SIV)-infected rhesus macaques for reduction of viral load to undetectable levels. Prolonged treatment of macaques with a high dose of PMPA (9-[2-(r)-(phosphonomethoxy) propyl] adenine or tenofovir; 30 mg/kg of body weight subcutaneously once daily) can result in proximal renal tubular dysfunction, a Fanconi-like syndrome characterized by glucosuria, aminoaciduria, hypopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In building our model of allo-HCT during suppressed SHIV infection, we encountered several challenges. First was the risk of renal insufficiency, a well-described toxicity of cART, most commonly attributed to tenofovir 56 , 57 . NHP transplant recipients were treated with cART for at least 6 months pre-transplant, and then continued to receive drugs post-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…In building our model of allo-HCT during suppressed SHIV infection, we encountered several challenges. First was the risk of renal insufficiency, a well-described toxicity of cART, most commonly attributed to tenofovir 56 , 57 . NHP transplant recipients were treated with cART for at least 6 months pre-transplant, and then continued to receive drugs post-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study conducted at Chiang Mai University Hospital, Thailand showed that lower baseline CD4 cell count was one of the main factors significantly associated with ART failure. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Renal toxicity with either acute or chronic overdosage of PMPA has been demonstrated but can be avoided with appropriate dosing [52,63]. While the NRTIs didanosine (ddI) and stavudine (d4T) have demonstrated anti-SIV activity, a significant proportion of macaques receiving this regimen have developed diabetes after >25 weeks of dosing, likely due to ddI toxicity [8,56].…”
Section: Cart Drugsmentioning
confidence: 99%